2015
DOI: 10.1002/marc.201500030
|View full text |Cite
|
Sign up to set email alerts
|

Stille Catalyst‐Transfer Polycondensation Using Pd‐PEPPSI‐IPr for High‐Molecular‐Weight Regioregular Poly(3‐hexylthiophene)

Abstract: A commercially available palladium N-heterocyclic carbene (Pd-NHC) precatalyst is used to initiate chain-growth polymerization of 2-bromo-3-hexyl-5-trimethylstannylthiophene. The molecular weight of the resultant poly(3-hexylthiophene) can be modulated (7 to 73 kDa, Đ = 1.14 to 1.53) by varying the catalyst concentration. Mass spectrometry data confirm control over the polymer end groups and (1)H NMR spectroscopy reveals that the palladium catalyst is capable of "ring-walking". A linear relationship between Mn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 40 publications
2
59
0
Order By: Relevance
“…With all these advances, only the IPr ligand has been used in controlled polymerization to date. PEPPSI‐IPr, a powerful palladium precatalyst developed by Organ and co‐workers has been employed in Kumada–Corriu, Suzuki–Miyaura and Stille–Migita CTP . Considering the wide range of carbene ligands that have been developed in recent years, these structures seem like excellent targets to prepare new metal catalysts for CTP.…”
Section: Discussionmentioning
confidence: 99%
“…With all these advances, only the IPr ligand has been used in controlled polymerization to date. PEPPSI‐IPr, a powerful palladium precatalyst developed by Organ and co‐workers has been employed in Kumada–Corriu, Suzuki–Miyaura and Stille–Migita CTP . Considering the wide range of carbene ligands that have been developed in recent years, these structures seem like excellent targets to prepare new metal catalysts for CTP.…”
Section: Discussionmentioning
confidence: 99%
“…Scheme 5 Synthesis of P3HT using a Pd-NHC catalyst [43]. reaction, Pd-or Ni-catalyzed cross-coupling reactions between organozincs and aryl, alkenyl, or alkynyl halides, was reported by Negishi and co-workers [44].…”
Section: Methodsmentioning
confidence: 96%
“…To obtain controlled polymers, the chain growth mechanism also needs to be introduced to this polymerization. Recently, a commercially available palladium N-heterocyclic carbene (NHC) complex (i.e., Pd-PEPPSI-IPr) was used to induce Stille catalyst transfer polycondensation of an AB-type monomer, i.e., SnHTBr (Scheme 5) [43]. The resultant high molecular weight poly(3-hexylthiophene) (P3HT) was regioregular, and the polymer length could be modulated (M n =7-73 kDa, PDI=1.10-1.53) by varying the catalyst concentration.…”
Section: Stille Polymerizationmentioning
confidence: 99%
“…Regarding the control of molecular weight and dispersity of D–A π‐conjugated alternating copolymers, catalyst‐transfer condensation polymerization (CTCP), which proceeds in a chain‐growth polymerization manner, of monoaromatic AB monomers through Kumada–Tamao, Suzuki–Miyaura, Negishi, Murahashi, or Stille coupling reactions has been extended to CTCP of D–A biaryl and D–A–D teraryl monomers to afford D–A π‐conjugated alternating copolymers with defined molecular weight and low dispersity. Kiriy and co‐workers first demonstrated that thiophene–thiophene ( D –D) biaryl monomers underwent Ni‐catalyzed Kumada–Tamao CTCP .…”
Section: Introductionmentioning
confidence: 99%
“…[9] Higashihara and co-workers reporteds imilar Stille coupling copolymerizationso fd istanylthiophene (D) and excess dibromonaphthalenediimide (A), but did not mention the polymer end groups. [10] Regarding the control of molecular weight and dispersity of D-A p-conjugated alternating copolymers, catalyst-transfer condensation polymerization (CTCP), which proceeds in ac hain-growthp olymerization manner,o fm onoaromatic AB monomers through Kumada-Tamao, [11] Suzuki-Miyaura, [12] Negishi, [13] Murahashi, [14] or Stille [15] couplingr eactions has been extendedt oC TCP of D-A biaryl and D-A-D teraryl monomers to afford D-A p-conjugated alternating copolymers with defined molecular weightand low dispersity.Kiriy and co-workers first demonstrated that thiophene-thiophene( D-D) biaryl monomers underwent Ni-catalyzed Kumada-Tamao CTCP. [16] Bielawski and co-workers synthesized thiophene-phenylene [17] (D-D) and thiophene-benzotriazole [18] (D-A) biaryl monomers and then conducted Kumada-Tamao CTCP of these monomers in ac ontrolled manner.H uck and co-workerss ynthesized fluorene-benzothiadiazole (D-A) alternating copolymer by means of Suzuki-Miyaura CTCP by using tBu 3 PPd as the initiator.…”
mentioning
confidence: 99%